A framework for evaluating and optimizing the cascade utilization of medium-low grade waste heat in marine dual-fuel engines. (10th December 2020) - Ouyang, Tiancheng; Su, Zixiang; Yang, Rui; Li, Changzheng; Huang, Haozhong; Wei, Qifeng
Abstract: Waste heat recovery technology performs a significant function in energy conservation and pollution reduction. It is also an effective means for alleviating the current global pollution and energy shortage. For this purpose, an combined system, which includes a supercritical carbon dioxide Brayton cycle, a low-temperature Rankine cycle, an absorption refrigeration system, and a capillary seawater desalination system, is established. The accuracy of the system is primarily verified by comparing its results with those found in existing literature. Some sensitive parameters that affect system performance are subsequently analyzed step by step, and the performance of the subsystem under the maximum continuous operational load condition is determined. The electricity production, fresh water mass flow, and cold energy are found to be 123.97 kW, 138.82 kg/h, and 86.48 kW, respectively. Considering the contribution of the low-temperature waste heat recovery device, the equivalent electricity production of the combined system is optimized by genetic algorithm. After obtaining the optimal operational condition, the thermodynamic performance, economic performance, and energy evaluation indexes are calculated. The results demonstrate that low-temperature waste heat recovery devices can operate in a wide range of load conditions, and the electricity production, energy efficiency, and exergy efficiency of the combined system are 222.31 kW, 23.19%, and 75.29%, respectively. Compared with the original engine system, the thermodynamic and emission reduction performance significantly improve, hence, this design is economically feasible and is an effective technology for energy saving, emission reduction, and energy cascade utilization. Graphical abstract: Image 1 Highlights: An framework for integrated cooling, desalination and power systems is proposed. Selecting suitable zeotropic mixtures to improve the system performance. The dynamic matching, analysis and optimization among subsystems are realized. The effect of engine injection strategy on waste heat recovery device is considered. The output power, energy and exergy efficiency reach 222.31 kW, 23.19% and 75.29%.